A new technique generation ghost-signal by microring resonator for 1.3_m security communication - U. Dunmeekeaw; S. Sririsin; N. Pornsuwancharoen; S. Chaiyasoonthorn; P.P. Yupapin; R. Phromloungsri (My University, 2012)
We present a new system of signal security using nonlinear micro ring resonators for optical communication system. When a Gaussian pulse (1.3 μm) is input into the system, the chaotic signal is generated and multiplexed into the optical communication. The chaotic waveform can be canceled using an add/drop device connected into the transmission link. In application results from the fact that the fast and slow light behaviors can be presented and can be seen using the add/drop filter. We can generate signal to obtain the two identical "signal" and "ghost" signals, which are observed in a different time frame. In this application, communication security can be performed when the required information is multiplexed and performs the link using the chaotic signal, signal and ghost signals, where the original signal can be retrieved and randomized by the known user.
Keywords: SIGNAL (programming language); Photonic and Optical Devices